Passive forensics for video object removal tampering - Ye YAO; Wei-tong HU; Yi-zhi REN (网络与信息安全学报)
Firstly, the concept and importance of digital video object removal tampering forensics were introduced. Then, several current passive forensics algorithms for object removal tampering were selected and divided into two categories that based on correlation analysis and based on machine learning algorithm according to development trends. The selected passive forensics algorithms were introduced in detail. Finally, some possible research trends in video object removal tampering detections in the future were looked forward to.